Association of Triglyceride/HDL Cholesterol Ratio with CRP and Ferritin among Different Obesity Phenotypes of Non-diabetic Adult Bangladeshi - TB, Waheed; MM, Hoque; SN, Chowdhury; A, Tasnim; R, Romana; M, Moyenullah; A, Alam (Archives of Clinical and Biomedical Research, 2025)
Introduction: Obesity is one of the major global problems now a days which is associated with insulin resistance and inflammation. Considering financial condition of Bangladesh, TG/HDL-c ratio can be used for assessment of IR. As CRP and ferritin usually respond to any type of inflammatory condition, they are expected to be raised in obesity. Early detection of association between TG/HDL-c ratio and inflammatory markers (CRP & ferritin) can help in prediction of severity of obesity induced health risks. Materials and Methods: A cross sectional analytical study was conducted in the Department of Biochemistry, Bangladesh Medical University (BMU) with 512 samples. Fasting blood sample and 2 hours after 75gm glucose load blood sample were collected for lipid profile, CRP & ferritin. BMI was calculated. Obese individuals were classified into three phenotypes named as phenotype A (obese BMI ,non-obese WC), phenotype B (non-obese BMI, obese WC) and phenotype C (obese BMI,obese WC). TG/HDL-c ratio was calculated and serum ferritin and CRP were assessed of different obesity phenotypes. Then correlation between TG/HDL-c ratio and CRP as well as ferritin was done to see their association in different obesity phenotypes. Results: TG/HDL-c ratio was significantly higher in phenotype B & C compared to phenotype A. Plasma CRP and ferritin level were found to be highest in phenotype C in comparison to phenotype A & B. Among phenotype C individuals, a positive correlation was found between TG/HDL-c ratio and serum ferritin but not with CRP and low positive correlation was found between CRP and ferritin. Conclusion: A significant association was shown between TG/HDL-c ratio and serum ferritin among phenotype C. Plasma CRP showed no significant association with TG/HDL-c ratio among different obesity phenotypes.